Pengaruh Pemberian Ensim Amilase terhadap Kadar Bioetanol dari Limbah Sagu Padat - Muhammad Lukman Hakim; Endah Dwi Hastuti; Sarjana Parman (Jurnal Akademika Biologi, 2015)
Sago starch processing industry in the village Plajan leaving solid waste that pollute the environment. Solid sago waste still contains carbohydrates ± 84.7%, which can be used as a base  material  for  bioethanol  production.  Giving  amylase  enzyme  in  this  study  aims  to optimize the starch hydrolysis process into glucose so as to increase the levels of bioethanol. The purpose of this  study was to determine the effect of amylase enzyme with different volumes on levels of bioethanol. The research methods include hydrolysis, fermentation and distillation.  The  study design  used  was  completely randomized  design  (CRD)  with  four treatments. Such treatment is A = 0 ml of α-amylase and glucoamylase 0 ml (control), B = 2 ml α-amylase and 2 ml of glucoamylase, C = 4 ml of α-amylase and glucoamylase 4 ml, D =6  ml  of α-amylase  and  6  ml  glucoamylase  three  replications.  Parameters  observed  that glucose levels,  levels of ethanol, and the volume  of bioethanol. Analysis  of the data by Analysist  Variance (ANOVA),  followed by Duncan's Multiple Test Test (DMRT). These results indicate that  administration of amylase enzyme is able to increase levels of ethanol until a certain volume. The most effective enzyme volume to produce the highest levels of bioethanol is the range of volume 2  ml α-amylase and 2 ml glucoamylase to 4 ml of α- amylase and 4 ml glucoamylase of ethanol  grading 63.33% to 69.00% with a distillation process the distillation temperature between 70-90oC.Keywords: Amylase, bioethanol, sago solid waste.